HUBUNGAN PATRON KLIEN PEDAGANG "NASI KUCING " DI KOTA YOGYAKARTA - Sri Emy Yuli Suprihatin (Jurnal Penelitian Humaniora, 2002)
Abstract In this study, the problem was that what the relation between the patron and clients of the “nasi kucing” sellers was like in Yogyakarta Municipality. The method of the study used was the analytic description with a qualitative approach. The collection of data is performed by thoroughly interviewing the informant. Data found from through interview are analyzed qualitatively. Based on these results, it can be concluded that (1) the relation between the patron and clients among the “nasi kucing” seller occurs due to the weakness of the human-resources of the “nasi kucing” sellers, unreliability of the relationship system to support the “nasi kucing” seller to run their economic activities and to fulfill their daily needs. (2) though there was such a patron and client relation, this occur temporary till the clients can be potentially self-sufficient. Keywords: the relation between the patron and clients, the master